Implementation Of Good Forest Governance In Forest Management In Indonesia - Yolamalinda, Yolamalinda; Widyawati, Laili Fuji; Istiqomah, Asti (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2023)
Land cover in Indonesia's forest areas is dynamic and can change rapidly with factors including the conversion of forest areas for use in other sectors; unsustainable forest management; illegal logging; unsustainable mining activities; disturbance; and forest fires, ineffectiveness and failure to optimize reforestation and land rehabilitation have also contributed to an increase in the area of ​​highly degraded land. Therefore, it is necessary to make significant improvements to the system and structure of forest governance to ensure that forest management is more sustainable and equitable, and not prone to corrupt practices. The aims of this paper are (a) to review the 2014 Forest Governance Index; (b) Analyzing the latest developments in Indonesia's Forest Performance; and (c) Analyze Indonesia's current e-government index and forest governance strategy. The results show that the transparency aspect is the weakest aspect in Indonesian forest governance in 2014 which indicates the need for systemic improvements to control the rate of deforestation and forest degradation related to corrupt practices. Currently, the government continues to make improvements and innovations in implementing good governance in the forestry sector. Forest management policies continue to meet new paradigms and national, regional and global strategic challenges such as meeting the demands of the SDG's and other international agreements. For Indonesia's e-government Development Index continues to experience improvement. For online service indexes, technology and service provision are the most important components to be improved. Meanwhile, for the telecommunication infrastructure index, the component of fixed broadband subscriptions is still weak. Steps to eradicate corruption through improving e-government can increase the effectiveness of regional development governance and performance.